2015
DOI: 10.1097/fpc.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants within immune-modulating genes influence the risk of developing rheumatoid arthritis and anti-TNF drug response

Abstract: Our data suggest that IL4 and IL8RB loci may have a small-effect genetic impact on the risk of developing RA, whereas IFNG might be involved in modulating the response to anti-TNF drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…In total, 47 studies were included in the analysis; 42 candidate gene studies 14 , 15 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 and 5 genome-wide association studies (GWAS) 60 , 61 , 62 , 63 , 64 analysing responders versus non-responders from anti-TNF therapy in RA ( Table 1 ). Two studies reported associations between polymorphisms and treatment response in juvenile idiopathic arthritis (JIA) 37 , 50 and the others on adult RA.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 47 studies were included in the analysis; 42 candidate gene studies 14 , 15 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 and 5 genome-wide association studies (GWAS) 60 , 61 , 62 , 63 , 64 analysing responders versus non-responders from anti-TNF therapy in RA ( Table 1 ). Two studies reported associations between polymorphisms and treatment response in juvenile idiopathic arthritis (JIA) 37 , 50 and the others on adult RA.…”
Section: Resultsmentioning
confidence: 99%
“…The Ethics committee of each participant institution approved the study protocol: Virgen de las Nieves University Hospital (2012/89); Santa Maria Hospital-CHLN (CE 877/121.2012); University Clinical Hospital of Santiago de Compostela (2013/156). A detailed description of the discovery population has been reported elsewhere [22][23][24] .…”
Section: Methodsmentioning
confidence: 99%
“…86,87 A recent study of 1239 participants found that patients with the IFNGrs2069705C allele had a significantly better response to TNF blocking therapy than did those carrying the wild-type allele. 88 As another example, various transforming growth factor b1 single nucleotide polymorphisms SNPs were associated with a good response to rituximab treatment. 89 Two studies have suggested a potential role for BAFF gene 871C>T promoter polymorphism and the 158 V/F polymorphism of FcGR3A in prediction of response to rituximab treatment.…”
Section: Genetics and Genomics In Prediction Of Response To Biologicamentioning
confidence: 99%